2008
DOI: 10.1007/s10067-008-0980-3
|View full text |Cite
|
Sign up to set email alerts
|

The frequency of sacroiliitis in familial Mediterranean fever and the role of HLA-B27 and MEFV mutations in the development of sacroiliitis

Abstract: The objective of this study was to investigate the frequency of sacroiliitis in familial Mediterranean fever (FMF) patients and the role of HLA-B27 and MEFV mutations in the development of sacroiliitis. The study group consisted of 256 FMF patients (male 128, female 128, mean age 27.2 +/- 6.3 years). After evaluation of the medical records, 70 patients (27.4%) were determined to have one or more of musculoskeletal manifestations. Sacroiliitis was determined in 18 (32.7%) FMF patients. The frequency of sacroili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
52
3
11

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(78 citation statements)
references
References 13 publications
8
52
3
11
Order By: Relevance
“…On the other hand, the absence of HLA B27 and lumbar spinal involvement are considered to be characteristics of FMF musculoskeletal manifestations (8,21,22). The frequency of sacroiliitis in FMF patients has been reported to be higher than expected in Turkish patients (20,21). In our experience, AS is common in FMF patients and has a more severe disease course.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…On the other hand, the absence of HLA B27 and lumbar spinal involvement are considered to be characteristics of FMF musculoskeletal manifestations (8,21,22). The frequency of sacroiliitis in FMF patients has been reported to be higher than expected in Turkish patients (20,21). In our experience, AS is common in FMF patients and has a more severe disease course.…”
Section: Discussionsupporting
confidence: 47%
“…Some authors suggested that FMF may be included in the spectrum of diseases with seronegative spondyloarthropathy (8). On the other hand, the absence of HLA B27 and lumbar spinal involvement are considered to be characteristics of FMF musculoskeletal manifestations (8,21,22). The frequency of sacroiliitis in FMF patients has been reported to be higher than expected in Turkish patients (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…However, in less than 10% of patients arthritis runs a more complicated pro-tracted course leading to functional disability and potentially prosthetic joint replacement [5][6][7]. There is a well-established link between FMF and ankylosing spondylitis (AS) where sacro-iliitis prevalence is estimated to be 7% in those with musculoskeletal manifestations [8]. The exact role of HLA-B27 in the development of sacro-iliitis is still controversial [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…There is a well-established link between FMF and ankylosing spondylitis (AS) where sacro-iliitis prevalence is estimated to be 7% in those with musculoskeletal manifestations [8]. The exact role of HLA-B27 in the development of sacro-iliitis is still controversial [8,9]. On the other hand, it has been established that M694V mutation is associated with the most severe clinical form of FMF.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation